Al–Pt compounds catalyzing the oxygen evolution reaction. Issue 5 (16th January 2023) - Barrios Jiménez, Ana María; Sichevych, Olga; Spanos, Ioannis; Altendorf, Simone G.; Ormeci, Alim; Antonyshyn, Iryna
Abstract : Al–Pt compounds have been systematically studied under conditions of the oxygen evolution reaction (OER). Abstract : Al–Pt compounds have been systematically studied as electrocatalysts for the oxygen evolution reaction (OER). Considering the harsh oxidative conditions of the OER, all Al–Pt compounds undergo modifications during electrochemical experiments. However, the degree of changes strongly depends on the composition and crystal structure of a compound. In contrast to Al-rich compounds (Al4 Pt and Al21 Pt8 ), which reveal strong leaching of aluminum, changes in other compounds (Al2 Pt, Al3 Pt2, rt-AlPt, Al3 Pt5, and rt-AlPt3 ) take place only on the surface or in the near-surface region. Furthermore, surface modification leads to a change in the electronic structure of Pt, giving rise to the in situ formation of catalytically more active surfaces, which are composed of intermetallic compounds, Pt-rich Al x Pt1− x phases and Pt oxides. Forming a compromise between sufficient OER activity and stability, Al2 Pt and Al3 Pt2 can be considered as precursors for OER electrocatalysts.